Handling noise complaints through conflict resolution in Toronto - Andréew, C.; Walker, K.; Rockhill, N. (Canadian Acoustics, 1993)
The Conflict Resolution Service, a program of St. Stephen’s Community House, was initiated in Toronto in 1985. The Conflict Resolution Service (CRS) is a community based program providing dispute resolution services to help resolve neighbourhood, landlord/tenant, intra-organizational and inter-personal disputes. The CRS approach to mediation is based on conciliation and empowerment of the individuals involved in conflict situation, emphasizing improved communication which leads to shared problem solving and more amicable relationships